Do Children Interpret 'or' Conjunctively?. (11th March 2020) - Skordos, Dimitrios; Feiman, Roman; Bale, Alan; Barner, David
Abstract: Preschoolers often struggle to compute scalar implicatures involving disjunction ( or ), in which they are required to strengthen an utterance by negating stronger alternatives, e.g. to infer that, 'The girl has an apple or an orange' likely means she does not have both. However, recent reports surprisingly find that a substantial subset of children interpret disjunction as conjunction, concluding instead that the girl must have both fruits. According to these studies, children arrive at conjunctive readings not because they have a non-adult-like semantics, but because they lack access to the stronger scalar alternative and, and employ doubly exhaustified disjuncts when computing implicatures. Using stimuli modelled on previous studies, we test English-speaking preschoolers and replicate the finding that many children interpret or conjunctively. However, we speculate that conditions which replicate this finding may be pragmatically infelicitous, such that results do not offer a valid test of children's semantic competence. We show that when disjunctive statements are uttered in contexts that render the speaker's intended question more transparent, conjunctive readings disappear almost entirely.